The Effect of Situational Factor, Visual Merchandising, and Electronic Word of Mouth on Impulsive Buying Behavior on Video on Demand Services Current The Covid-19 Pandemic Crisis - Muhammad Saif Furqan Abdullah; Yessy Artanti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
The COVID-19 pandemic situation makes people tend to consume video on demand as an alternative for home entertainment. This makes video on demand service providers compete by taking advantage of this situation. Sometimes the existing stimulus can lead people to buy products impulsively. This study aims to examine the effect of situational factor, visual merchandising, and electronic word of mouth on impulse buying behavior. This study used non-probability sampling techniques and the method used was judgmental sampling. This study focuses on Netflix consumers aged 18-39 who bought Netflix products impulsively during the COVID-19 pandemic. 200 respondents collected using the online bilingual questionnaire in English and Indonesian and spread over 32 countries. Data were analyzed using a multiple linear regression method. The results showed that situational factor and electronic word of mouth significantly influence on impulse buying behavior. Meanwhile, visual merchandising has no influence on impulse buying behavior. This can be used as a reference in increasing sales by maximizing consumer impulse buying behavior.